Identification and Toxicity Evaluation of Water-Soluble Chemicals Generated by the Photooxidative Degradation of Expanded Polystyrene - Lee, Seulgidaun; Alam, Md Badrul; Jung, Maeng-Joon; Lee, Sangkyu; Liu, Kwang-Hyeon; Lee, Sang-Han; Kim, Sunghwan (Frontiers in Environmental Science, 2022)
In this study, expanded polystyrene (EPS) was photodegraded in vitro, and its water-soluble degradation products were extracted using solid-phase extraction. An in vivo test using the MTT assay showed that EPS exhibited increased toxicity upon photodegradation. This clearly demonstrates the necessity of investigating the degradation products at a molecular level, and thus, we conducted analyses using high-resolution mass spectrometry coupled with liquid chromatography. Overall, 68 compounds were detected, of which 13 were identified after comparing the retention times and tandem mass spectra of the extracted compounds with those of standards. The toxicity of the degraded EPS was studied by examination of the detected compounds combined with published reports. In addition, the quantification of the most abundant compounds showed that discarded EPS can generate a significant amount of chemicals by UV degradation. The data in this study show that degraded EPS can pose a significant environmental threat as a source of potentially hazardous chemicals. This study provides a fundamental basis for the evaluation of the fate and toxicity of photodegraded EPS.